The Interplay Between Economic Policy, Oil Price and Economic Growth in Malaysia - Siow, Xiu Yun; Tsen, Wong Hock (Ekonomika, 2025)
This study examines the interactions among the oil price, Government expenditure, money supply, real effective exchange rate, and Gross Domestic Product (GDP) across Malaysia’s finance, retail and wholesale, manufacturing, agriculture and overall sectors by using a Structural Vector Autoregression (SVAR) model. The variance decomposition has revealed an increasing interconnectedness among the variables over time, with external factors such as global commodity prices and fiscal policies becoming more significant in shaping sectoral dynamics. The impulse response function analysis highlighted sector-specific variations: the finance and retail sectors predominantly exhibited positive responses to the oil price and GDP shocks, while the agriculture sector showed mixed responses, reflecting its reliance on external and policy-driven factors. The manufacturing sector displayed sensitivity to monetary conditions, while the overall sectoral trends suggested the ability to absorb shocks effectively. The findings highlight the need for sector-specific policies so that to enhance Malaysia’s economic resilience and achieve SDG 8, advising policymakers to adopt adaptive fiscal and monetary measures, strengthen agricultural resilience, and promote diversification in the retail and manufacturing sectors for inclusive and sustainable growth.
Keywords: Oil Price; Economics Policy; Real Effective Exchange Rate; Gross Domestic Product; Structural Vector Autoregression; Impulse Response